LEGAL REGULATION OF SALES OF LAND FACILITIES AGRICULTURAL APPOINTMENT IN UKRAINE - Корнєєв, Юрій Валентинович; Козирєва, Валентина Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the article explores the concept and essence of a moratorium on the sale of agricultural land, defines the objects of the moratorium and the circle of subjects on which it is distributed. Methods of research: used methods of analysis, comparison and synthesis. Results: it is suggested that the introduction of the land market is possible only in the presence of full state protection of agrarian sector. The analysis of the impact of the moratorium on the state economy has also been made, conclusions have been formulated on the expediency of extending the moratorium on the sale of agricultural land. Nowadays, the legislation of Ukraine refers those lands that have a specific intended purpose to agricultural lands - their use is allowed, directly in agricultural production. In accordance with part 1 of Article 22 of the Land Code of Ukraine, agricultural land is recognized as land for agricultural production, agricultural research and development activities, the placement of the corresponding production of infrastructure, including the infrastructure of wholesale agricultural markets, or intended for these purposes. Purchase and sale or other means of alienation of the abovementioned land plots and land shares shall be introduced in accordance of the enactment of the law on the circulation of agricultural land, but not earlier than January 1, 2016, in accordance with the procedure established by the law. We can conclude that nowadays, there is no consensus on the abolition of the moratorium does exist; it is necessary to substantiate scientifically and expediency of decisions on the launch of the land market. Until now, it is not clear whether there will be restrictions on the maximum amount of land resources that can be concentrated in one’s hands? Will foreigners be allowed to buy land? Who will check the transparency of land purchase deals, etc.? By analyzing the scientific publications of well-known scientists, economists, taking into account the positive and negative aspects of the existing moratorium on the sale of agricultural land. However, in any case, addressing the current problem will affect geopolitical and economic interests. Many issues according to this field of study require further study and resolution. Therefore, it is important and urgent today to consolidate the legal and organizational foundations in the land market.